Ethnobotany of the Vile Shard Plant (strobilanthes crispa (L) blume) As a Cure for Diabetes in the People of the Nias Islands - Etti Sartina Siregar (International Journal of Ecophysiology, 2022)
The use of medicinal plants by the Indonesian people has been carried out for a long time from generation to generation to cure certain diseases, one of which is the people of the Nias Islands who use the vile shard leaves ( Strobilanthes crispa (L. ) (Blume) as a drug to reduce urinary complaints, kidney stones, gallstones and diabetes. Keji shard leaves are known to have high antioxidant compounds, namely flavonoids which can be used as medicinal compounds to treat diabetes, hypertension and inhibit the growth of pathogenic bacteria such as Escherichia coli, Staphylococcus aureus and Streptococcus pyogenes